Melatonin as an Anti-Aging Therapy for Age-Related Cardiovascular and Neurodegenerative Diseases - Martín Giménez, Virna Margarita; de las Heras, Natalia; Lahera, Vicente; Tresguerres, Jesús A. F.; Reiter, Russel J.; Manucha, Walter (Frontiers in Aging Neuroscience, 2022)
The concept of "aging" is defined as the set of gradual and progressive changes in an organism that leads to an increased risk of weakness, disease and death. This process may occur at the cellular and organ level, as well as in the entire organism of any living being. During aging, there is a decrease in biological functions and in the ability to adapt to metabolic stress. General effects of aging include mitochondrial, cellular and organic dysfunction, immune impairment or inflammaging, oxidative stress, cognitive and cardiovascular alterations, among others. Therefore, one of the main harmful consequences of aging is the development and progression of multiple diseases related to these processes, especially at the cardiovascular and central nervous system level. Both cardiovascular and neurodegenerative pathologies are highly disabling and, in many cases, lethal. In this context, melatonin, an endogenous compound naturally synthesized not only by pineal gland, by also by many cell types, may have a key role in the modulation of multiple mechanisms associated with aging. Additionally, this indoleamine is also a therapeutic agent, which may be administered exogenously with a high degree of safety. For this reason, melatonin could become in an attractive and low-cost alternative for slowing the processes of aging and its associated diseases, including cardiovascular and neurodegenerative disorders.